2008
DOI: 10.1016/j.brainresbull.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Sustained activation and executive control in the avian prefrontal cortex

Abstract: We review our studies examining neural correlates of directed forgetting and executive control in the avian prefrontal cortex. One of the fundamental forms of executive control is the ability to selectively filter information, retaining that which is critical for the current purposes and discarding that which is not. In our first experiment, we trained birds on a directed-forgetting version of a delayed matching-to-sample task. Following a sample stimulus, a bird heard either a remember tone indicating that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…on a remember-cued trial (Kendrick et al, 1981; but see Grant and Barnet, 1991). Consistent with this interpretation of the different effects of forget cue trials depending on the events that followed the forget cue in training, Milmine et al (2008) found that neurons in the nidopallium caudolaterale (a proposed pigeon analog to the mammalian prefrontal cortex) differentially fired on remember and forget cues relative to the intertrial interval. However, in a second experiment they found when forget cue trials ended in reinforcement, the neurons showed the same neuronal activity levels as on remember cue trials.…”
Section: Directed Forgettingsupporting
confidence: 55%
“…on a remember-cued trial (Kendrick et al, 1981; but see Grant and Barnet, 1991). Consistent with this interpretation of the different effects of forget cue trials depending on the events that followed the forget cue in training, Milmine et al (2008) found that neurons in the nidopallium caudolaterale (a proposed pigeon analog to the mammalian prefrontal cortex) differentially fired on remember and forget cues relative to the intertrial interval. However, in a second experiment they found when forget cue trials ended in reinforcement, the neurons showed the same neuronal activity levels as on remember cue trials.…”
Section: Directed Forgettingsupporting
confidence: 55%
“…In the same vein, Rose and Colombo [4] found 67% of neurons with sustained delay activity, the majority of which responded only for a to-be-remembered stimulus, but not after the pigeon was instructed to forget the stimulus. Several follow-up studies demonstrated that this activity was based mainly on reward prediction [29][30][31]. Similarly, if different auditory stimuli are associated with one of two response keys, it is difficult to dissociate responses representing the associations or rather preparatory left versus right motor activity [32].…”
Section: Prospective Associative Signals In Ncl Neuronsmentioning
confidence: 98%
“…Divac and coworkers were the first to propose that the avian equivalent of the PFC is the NCL (Mogensen & Divac, 1982, 1993; Divac, Mogensen & Björklund, 1985). Since then a growing body of research has accumulated supporting the notion that the NCL and PFC are analogous structures involved in performing high‐order cognitive processes (Reiner, 1986; Güntürkün, 1997; Hartmann & Güntürkün, 1998; Braun et al , 1999; Kalt, Diekamp & Güntürkün, 1999; Diekamp, Kalt & Güntürkün, 2002; Rose & Colombo, 2005; Milmine, Rose & Colombo, 2008; reviewed in Güntürkün, 2005 a , b ; Kirsch, Güntürkün & Rose, 2008; Rose, Güntürkün & Kirsch, 2009). Although the PFC and NCL both develop from the pallium (dorsal portion of the neural tube), they originate from different pallial sectors, and therefore reflect analogous structures (see ).…”
Section: Avian Hippocampal Formation and ‘Prefrontal Cortex’mentioning
confidence: 99%